Vaccination recommendations for adult patients with autoimmune inflammatory rheumatic diseases (Swiss Medical Weekly, 2015)
BACKGROUND: The number of individuals with autoimmune inflammatory rheumatic diseases (AIIRDs) treated with immunosuppressive drugs is increasing steadily. The variety of immunosuppressive drugs and, in particular, biological therapies is also rising. The immunosuppressants, as well as the AIIRD itself, increase the risk of infection in this population. Thus, preventing infections by means of vaccination is of utmost importance. New Swiss vaccination recommendations for AIIRD patients were initiated by the Swiss Federal Office of Public Health and prepared by a working group of the Federal Commission for Vaccination Issues as well as by consultation of international experts. METHODS: A literature search was performed in electronic databases (Cochrane, Medline, PubMed, Embase). In addition, unpublished literature was identified through a targeted website search of relevant organisations and international conferences dealing with vaccination, infectious diseases and rheumatology. RESULTS: Although data are scarce, the following main points were retrieved from the literature. Inactivated vaccines are safe, but their immunogenicity may be reduced in AIIRD patients, especially if they are under immunosuppressive therapy. Rituximab and abatacept appear to reduce significantly immune responses after vaccination. Live vaccines are generally contraindicated under immunosuppressive therapy owing to safety concerns. Specific exceptions, as well as time intervals for the administration of live vaccines after interruption of an immunosuppressive therapy, have been formulated in this article. CONCLUSION: More evidence regarding the immunogenicity and safety of vaccinations in AIIRD patients under various therapies is needed. Vaccination recommendations should be updated on a regular basis, as more scientific data will become available.